FORMULASI KRIM ANTI-AGING DARI EKSTRAK EKSTRAK ETANOL KACANG HIJAU (Phaseolus radiatus Roxb. Non-L.) - Nurbaya, Siti; Br Brahmana, Nettietalia; Rejekinta Munthe, Alfian; Pangaribuan, Novalina (JURNAL TEKNOLOGI KESEHATAN DAN ILMU SOSIAL (TEKESNOS), 2021)
Background: green beans are one type of peanut that are widely consumed by communities as functional. The green nut contains a secondary metabolic compound, among them flavonoid, saponin, steroid/triterpenoid, and tannin, which are potent antioxidants.Research goals: for this study, there is an introduction to the new anti-aging activity in green beans ethanol (Phaseolus radiatus Roxb. non-L..). Research methods: this research method USES experimental methods with 5% concentration, 10%, and 15%. Then compared to the availability in the market and blanks. Some tests have been made against availability, including physical qualities of ready cream including homosexual, existing stability observations, pH, viscosity tests of volunteers, and anti-aging activities of volunteers. Results: the results from the study are the result of a stable cream test at room temperature for four weeks. Organoleptic results in Blanko’s formula and control formulas have not undergone any discoloration, changes in smell and phase separation after four-week long storage of ph cream meet good requirements in skin ph, no side effects of irritation and availability of green bean extract cream (Phaseolus radiatus Roxb. Non-L.) can demonstrate anti-aging effectiveness at 15% concentration. Conclusion: research suggests that supple green bean extract cream has an anti-aging activity.